Dynamics of Social Interaction on Psychological Well-Being among College Students - Salsabila Nashwa Aslamina; Alia Zahra Fitriani; Rabitha Khusna Riyantaka (Philanthropy: Journal of Psychology, 2024)
Social interaction plays an important role in improving students' psychological well-being, especially in higher education environments. This study aims to analyze the effect of social interaction on students' psychological well-being. The research method used is quantitative, with a population of 240 students and a sample of 142 students. The sample was selected through a simple random sampling technique, and analyzed using a simple linear regression analysis technique. The results of the study showed a significant relationship between social interaction and psychological well-being, with a regression coefficient value of 0.254 and a p value